Long term follow up of SHR rats with experimental yersinia associated arthritis. Issue 1 (January 1992) - Merilahti-Palo, R; Gripenberg-Lerche, C; Söderström, K O; Toivanen, P
Abstract : One hundred and one SHR rats were injected intravenously with live Yersinia enterocolitica O:8. The rats were randomly divided into two groups consisting of 48 and 53 rats. The group of 48 rats was monitored for 245 days to establish the incidence and the clinical features of the arthritis. The remaining 53 rats were killed in groups of three to five rats at intervals from four to 245 days after inoculation to examine the clearance of bacteria and the development of histological changes in the synovial membrane. Arthritis developed in 23/48 (48%) rats at seven to 27 days after inoculation. The arthritis subsided in most rats within four weeks, without leading to ankylosis of the affected joints. The arthritis was prolonged in three rats and recurrent in two. In the group of 53 rats Yersinia enterocolitica O:8 was cleared from most of the internal organs by day 77, but persisted in the inguinal lymph nodes in many of the rats up to day 245. All macroscopically arthritic joints showed clear histological signs of non-suppurative synovitis. No histological synovitis was detected in those joints observed macroscopically to be non-arthritic. Yersinia associated arthritis in SHR rats provides a potential model for reactive arthritis. There are strong similarities in the course of the arthritis and histopathological changes in the synovium between this animal model and reactive arthritis in humans. This study supports the association between poor elimination of the causative agent and the development of arthritis.